IMPLEMENTASI KURIKULUM BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN KOMPETENSI GURU - Eko Susanti; Dirgantara Wicaksono (Taksasila Edukasi Insani, 2025)
This study describes the implementation of a local wisdom-based curriculum to improve teacher competency at TK Zema Ananda, Tangerang City. Employing a qualitative case study, data were gathered from the principal, teachers, and students through in-depth interviews, observations, and documentation. The analysis reveals a successful integration of local wisdom values into the curriculum, fostering teacher innovation in developing contextual, enjoyable, and culturally relevant learning activities. The research highlights that this implementation not only strengthens children's character and cultural identity from an early age but also significantly contributes to improving teacher competency. Key success factors include strong school leadership and the active involvement of parents and the community, which enriches the learning ecosystem. It is concluded that a local wisdom-based curriculum serves as an effective model for authentic professional development and holistic early childhood education, making learning more meaningful for children and empowering for teachers.Keywords : curriculum, local wisdom, teacher competence, kindergarten, Tangerang City